The Relationship Between the use of Computer-Based Technology and Digital Literacy Skills and the Achievement of SDG Goal 4 (Quality Education) in Primary Schools - Rena Dwi Wulandari; Unique Amber Wati; Gantheng Listyoadi (Journal of Educational Sciences, 2026)
This study aims to analyze the relationship between the use of computer-based technology and digital literacy skills and the achievement of SDG Goal 4 (Quality Education) in elementary schools. This study uses a correlation approach with a sample of 231 fifth-grade elementary school students in Ngemplak District, selected through purposive sampling from five schools that have implemented educational technology and digital literacy programs. Data collection was carried out through observation, questionnaires, and documentation. The results of the reliability test showed a score of 0.872 for the use of computer-based technology, 0.956 for digital literacy skills, and 0.896 for the achievement of SDG Goal 4. Data analysis uses correlation, simple linear regression, and multiple linear regression. The results showed that: (1) there was a significant relationship between the use of computer technology and the achievement of SDG Goal 4 with a significance level of 0.000 and a correlation of 0.407, (2) there was a significant relationship between digital literacy skills and the achievement of SDG Goal 4 with a significance level of 0.000 and a correlation of 0.559, and (3) there was a significant high and simultaneous relationship between the use of computer technology and digital literacy skills on achievement of SDG Goal 4 with a significance level of 0.000 and a correlation of 0.559.